The distribution of aerosols over the Georgian territory in the lower troposphere - Amiranashvili, Avtandil; Amiranashvili, Vazha; Chochishvili, Ketevan; Kirkitadze, Darejan (Journals of Georgian Geophysical Society, 2014)
The vertical distribution of the number concentration of aerosols with sizes more than 0.35 mcm in radius has been studied for various regions of Georgia. In particular it was shown that within the lower five kilometer atmospheric layer the size distribution of aerosols is quite steady and varies little with elevation and under the influence of cloudiness. However at days with cumulus clouds in comparison to cloudless days the mass of aerosols in the lower five kilometer layer increases approximately 1.4 times, while at days with clouds of various types including cumulus – 2.5 times.